Potable Water Reuse through Advanced Membrane Technology - Tang, Chuyang Y; Yang, Zhe; Guo, Hao; Wen, Jason J; Nghiem, Long D; Cornelissen, Emile (Environmental science & technology, 2018)
Recycling water from municipal wastewater offers a reliable and sustainable solution to cities and regions facing shortage of water supply. Places including California and Singapore have developed advanced water reuse programs as an integral part of their water management strategy. Membrane technology, particularly reverse osmosis, has been playing a key role in producing high quality recycled water. This feature paper highlights the current status and future perspectives of advanced membrane processes to meet potable water reuse. Recent advances in membrane materials and process configurations are presented and opportunities and challenges are identified in the context of water reuse.